ASSOCIATED FACTORS WITH THE ISOLATED AND SIMULTANEOUS PRESENCE OF OVERWEIGHT AND ABDOMINAL OBESITY IN ADOLESCENTS - Tiago Rodrigues de Lima; Mikael Seabra Moraes; Joaquim Huaina Cintra Andrade; Joni Márcio de Farias; Diego Augusto Santos Silva (Sociedade de Pediatria de São Paulo, 2020)
ABSTRACT Objective: To analyze the sociodemographic and lifestyle factors associated with excessive weight (EW), abdominal obesity (AO) and the simultaneous presence of EW and AO in adolescents from Southern Brazil. Methods: Cross-sectional study with 583 adolescents (11 to 17 years old) of Criciúma, Santa Catarina, Brazil. EW was assessed by body mass index (BMI) and AO by waist circumference (WC). The independent variables analyzed were gender, age, maternal schooling, balanced diet, physical activity, cigarette use, excessive alcohol use and screen time. Binary logistic regression was used to estimate Odds Ratios (OR) and 95% confidence intervals (95%CI). Results: Boys had 58% higher likelihood of having EW (OR 1.58; 95%CI 1.08-2.29; p<0.05). Younger age group (11 to 14 years) was directly associated with higher likelihood of EW (OR 6.07; 95%CI 4.05-9.11; p<0.05). Adolescents whose mothers had higher education had 75% more likelihood of having AO (OR 1.75; 95%CI 1.01-3.00; p<0.05). Higher likelihood for EW and AO (OR 1.84; 95%CI 1.01-3.34; p<0.05) was identified in younger adolescents (11 to 14 years). Conclusions: Boys and younger age (11 to 14 years) were associated with a higher likelihood of EW. Adolescents whose mothers studied nine years or more were more likely to have AO. The younger age group (11 to 14 years) was associated with greater chances for the simultaneous presence of EW and AO.